PENGARUH KECERDASAN EMOSIONAL, LINGKUNGAN KERJA DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PADA PT. OSI ELECTRONICS - YULIA RESTI FAUZI; SUHARDI . (LP2MTBM MAKARIOZ, 2020)
This research was conducted to examine the effect of emotional intelligence, work environment and work culture onemployee performance at PT. Osi Electronics. This research includes associative research on a causal quantitativeapproach. This study uses a population of one department of PT. Osi Electronics' employees totaling 268 people and in thisstudy uses a non probability sampling technique so that if calculated using the solvin formula with an error rate of 5% so asto produce a sample of 161 people. Data collection used is by distributing questionnaires while data analysis using dataanalysis is done by using descriptive statistical analysis, Validity Test, Reliability Test, Classical Assumption Test (NormalityTest, Multicollinearity Test and Heteroskedastity Test), Influence Test (Multiple Linear Regression Analysis andDetermination Coefficient Analysis and Hypothesis Test (t Test and F Test). based on research from data analysis it can beconcluded that partially (T-test) emotional intelligence variable significantly and positively influences employee performancewith a value of 0,000 <0.05, work environment variables have a positive and significant effect on employee performance witha value of 0.001 <0.05, then the work culture also has a positive and significant effect on employee performance. whilesimultaneously (Test F) emotional intelligence, work environment and work culture variables have a positive and significanteffect on employee performance with a value of 0,000 <0.005.